Experimental investigation on a solar dryer integrated with condenser unit of split air conditioner (A/C) for enhancing drying rate. (July 2018) - Chandrasekar, M.; Senthilkumar, T.; Kumaragurubaran, B.; Fernandes, J. Peter
Abstract: In an indirect forced circulation solar dyer, solar thermal energy is primarily used for drying the commodities while electrical energy is used for operating the blower/fan to force air through the collector and drying chamber. In few applications, electrical energy is also being used in auxiliary heater to speed the drying process and assist drying during non sun shine hours. The aim of this research work is to eliminate the use of electricity in the indirect solar dryers by utilizing split A/C condenser unit that is placed outdoors. This idea will eliminate the electrical energy requirement for blower/fan to force air in the drying chamber and enable to use thermal energy dissipated from split A/C system as auxiliary heating source. For this purpose, an integrated solar dryer that uses hot air from split A/C condenser was fabricated in house and the drying behavior of sultana grapes was investigated in the present work. Drying experiments were carried out in the locality of Tiruchirappalli (78.6°E & 10.8°N), Tamil Nadu, India during summer months of April and May 2016. The use of split A/C condenser outlet cooling air reduced the drying time of grapes by 16.7% compared with open sun drying method. A possibility of 13% increase in solar dryer efficiency was demonstrated due to the integration of solar dryer with A/C condenser unit compared to the conventional indirect solar dryer. From the experimental results, it was found that the exponential model is capable of describing the drying characteristics of seedless grapes. Predicted values of moisture ratio were in good agreement with experimental values. The exergy analysis indicated increased heat availability inside the dryer chamber. Graphical abstract: Image Highlights: Solar dryer is integrated with air cooled condenser unit of split air conditioner (A/C). Due to this, electric power required for operating the fan and auxiliary heating is eliminated. Drying time of grapes is reduced by 16.7% compared with the open sun drying. Exergy in the drying chamber is increased due to recovery of heat rejected from A/C condenser.